Implementation Of A Genetic Algorithm To Determine The Minimum Spanning Tree (MST) In An Undirected Graph - Alfatah, Dhika (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This research is background by existence of problems of minimum spanning tree in graph which difficult to be finished so that require certain method to finishing it, despitefully there are also algorithm of genetic able to be made as method to finish the problems. The purpose of this research is applying algorithm of genetic to determine minimum spanning tree at undirected graph. Method scheme of system the used is Waterfall, while analysis method the used is Data Flow Diagram. For the data processing of, method the used is algorithm of genetic. While result of research known that algorithm of genetic earn implementation into application to determine minimum spanning tree.